Sistem Prediksi Pengiriman Pada Dakota Cargo Menggunakan Metode Naive Bayes Berbasis Web - Firmansyah, Moh Alfian; Alamin, Mochammad Machlul (STMIK Banjarbaru, 2024)
Sending goods on an expedition is the most important thing to support the progress of a shipping service company. This research aims to create a system that can predict whether goods delivery will be on time or late according to the estimates provided by the Dakota Cargo expedition using the Naive Bayes method. Classification using Naive Bayes is based on previous events, where the features used to classify data are independent of each other. The amount of goods delivery training data used is 509 data from historical data, then this data is implemented into a website-based application to form an application that can predict goods delivery. The implementation results can be seen from the value of each class, where the value becomes the benchmark for determining the prediction status of